Acute renal failure complicating Legionnaires' disease. Issue 659 (September 1980) - Harvey, M.; Quirke, P.; Warren, D.
Abstract : A 45-year-old man developed symptoms of pneumonia while on holiday in Spain. On his return home, a diagnosis of Legionnaires' disease was confirmed, complicated by acute renal failure, He was treated with dialysis and spontaneous recovery of renal function began on day 19.